Constrained Choices? Menstrual Health and Hygiene Needs Among Adolescents in Mumbai Slums. (February 2019) - Muralidharan, Arundati
Menstruation, an essential and healthy biological function, is cloaked in a culture of silence. Sociocultural norms at the family and community level play a pivotal role in shaping how young unmarried women understand and manage their monthly period. Less is known about how unmarried young women living in low-income urban areas in India seek help for their menstrual needs. This qualitative study seeks to understand how young unmarried women (aged 15–24) living in a slum settlement understand menstruation and perceive menstrual problems, and identifies factors that influence their help-seeking behaviour for menstrual needs and problems. It also proposes recommendations for national health programmes addressing menstrual health and hygiene. The findings echo previous research findings emphasising young unmarried women's low levels of awareness and misconceptions about menstruation. These girls perceived menstrual problems as a key concern, as it significantly interfered with their daily routine and caused emotional distress. Young women's ability and willingness to seek help to address menstrual needs is influenced by a culture of silence that surrounds menstruation, excessive scrutiny and blaming by the community, and restrictions on their mobility and interactions with peers. The findings underscore the role of mothers as gatekeepers who greatly influence young women's perceptions of menstruation and menstrual problems and their ability to seek help. Existing interventions need to be expanded to address young women's need for emotional and social support, and to involve significant gatekeepers such as mothers in promoting the health and well-being of young unmarried women in slum communities. Intervention strategies should be expanded to enhance the capacity of mothers to recognise, understand and address their teenage daughters' needs for information, emotional support and access to essential clinical and social services.